NICOLE - NEW ONLINE ORIENTATION FACILITY AT ISOLDE/CERN - Eder, R; Berkers, I; Brown, D; Grand, I; Hagn, E; Harding, P; Hassani, R; Herzog, P; Kastelein, B; Knipper, A; Marguier, G; Massaq, M; et al. (1990)
This paper presents off-line and on-line orientation results obtained with the new on line nuclear orientation device NICOLE in CERN. Magnetic moments of 187,185Pt g and 186Ir m, electric quadrupole moment ratios between Pt isotopes with mass number 185, 187 and 189, the spin of the 2 h isomer of 186Ir and a new decay scheme of 184Au involving a metastable state are established. The shape variation versus mass number of the Pt isotopes leads to sign change of the spectroscopic quadrupole moment between A=187 and 185. © 1990 J.C. Baltzer A.G., Scientific Publishing Company.